2022
DOI: 10.1155/2022/4373404
|View full text |Cite|
|
Sign up to set email alerts
|

Stereotactic Aspiration Acts as an Effective Treatment for Malignant Middle Cerebral Artery Infarction

Abstract: Objective. This study seeks to explore the efficacy and prognosis of stereotactic aspiration for malignant middle cerebral artery infarction (mMCAI). Methods. A total of 50 mMCAI patients who were diagnosed and treated in our hospital from January 2018 to June 2020 were collected and then randomly divided into control group (decompressive craniectomy, n = 24) and study group (stereotactic aspiration, n = 26). After 1 and 6 months of treatment, the scores of the National Institutes of Health Stroke Scale (NIHSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%